(Nproklqtye filxmy golliwudas - (Nwasilenko(B,(Na(B.s (Nannas (2010)
"(NiZGONQ@]IJ DXQWOLA(B" (1973 (NG(B.), "(NwOL[EBNIK STRANY oZ(B" (1939 (NG(B.), "(NrEBENOK rOZMARI(B" (1968 (NG(B.), (NTRILOGIQ (B"(NpOLTERGEJST(B" (1982-1988 (NGG(B.), "(NwORON(B" (1994 (NG(B.), "(NoMEN(B" (1976 (NG(B.), "(NsUPERMEN(B" (1951 (NG(B. (NI DALEE(B).s